2020
DOI: 10.1152/ajpcell.00166.2018
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of myosin heavy chain antisense long noncoding RNA in human vastus lateralis in response to exercise training

Abstract: Alterations to muscle activity or loading state can induce changes in expression of myosin heavy chain (MHC). For example, sedentary individuals that initiate exercise training can induce a pronounced shift from IIx to IIa MHC. We sought to examine the regulatory response of MHC RNA in human subjects in response to exercise training. In particular, we examined how natural antisense RNA transcripts (NATs) are regulated throughout the MHC gene locus that includes MYH2 (IIa), MYH1 (IIx), MYH4 (IIb), and MYH8 (Neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…For example, elderly individuals with sarcopenia primarily present with a loss of type II fibres, whereas chronic obesity is primarily associated with type I fibre atrophy. Recently, a number of studies have investigated the potential role of lncRNAs in the regulation of muscle fibre type 89–92 and have been associated with a switch in MHC expression from IIx to IIa in humans following a 5‐week exercise protocol 92 . Thus, it will be important to identify if similar lncRNA‐mediated changes in fibre type occur in the obese state.…”
Section: Lncrnas and Obesity‐associated Chronic Inflammatory Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…For example, elderly individuals with sarcopenia primarily present with a loss of type II fibres, whereas chronic obesity is primarily associated with type I fibre atrophy. Recently, a number of studies have investigated the potential role of lncRNAs in the regulation of muscle fibre type 89–92 and have been associated with a switch in MHC expression from IIx to IIa in humans following a 5‐week exercise protocol 92 . Thus, it will be important to identify if similar lncRNA‐mediated changes in fibre type occur in the obese state.…”
Section: Lncrnas and Obesity‐associated Chronic Inflammatory Diseasementioning
confidence: 99%
“…86 In a similar study, the novel atrophy-related lncRNA-1 (Atrolnc-1) was upregulated in the skeletal muscle of murine models of muscle wasting. 87 Furthermore, Atrolnc-1 was demonstrated to bind A20 binding inhibitor of NF-κB-1 (ABIN-1) in the cytoplasm of number of studies have investigated the potential role of lncRNAs in the regulation of muscle fibre type [89][90][91][92] and have been associated…”
Section: Sarcopenia and Skeletal Muscle Atrophymentioning
confidence: 99%
See 1 more Smart Citation
“…More and more evidence shows that voluntary exercise may restore the cognitive dysfunction of the elderly and exercise contributes to the alternation of lncRNAs' expression. [24][25][26] In a publication of heart protection, swimming can mitigate vascular endothelial ischemia-reperfusion injury by regulating FR030200-Col3A1 and FR402720-Rnd1, and the pattern of lncRNA THRIL regulating TNF-a may change after running 27,28 A further study of 2020 indicates that exercise-caused lncRNA MALAT1 protects hippocampal cells and cardiac muscle cells against ischemic diseases 29 In the current investigation, the AD mice were obtained to access the molecular mechanism of SNHG14. In the assay, we found that the expression of SNHG14 in the VE group was decreased, which showed that exercise might reduce the SNHG14 levels of AD mice.…”
Section: Discussionmentioning
confidence: 90%
“…For example, the combination of lncRNA and the chromatin remodeling complex promotes the formation of a dense chromatin structure, thereby generating gene-silencing regions [ 119 ]. lncRNA can also regulate histone modification [ 120 ], promote DNA methylation modification [ 121 ], inhibit transcription factors [ 122 ], and inhibit RNA polymerase II [ 123 ] to regulate mRNA expression, or NATs can directly interfere with mRNA expression, posttranscriptional processing, and transportation [ 112 , 124 , 125 ]. lncRNAs located in the cytoplasm are mainly involved in the regulation and transportation of protein translation.…”
Section: Ncrnamentioning
confidence: 99%